Time Students Spend Reading Threaded Discussions in Online Graduate Courses Requiring Asynchronous Participation - Brown, Abbie H.; Green, Tim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The authors report the results of a study that provides bases for comparison between the time necessary to participate in courses delivered asynchronously online and courses delivered in a traditional classroom setting. Weekly discussion threads from 21 sections of six courses offered as part of online, degree-granting, accredited, graduate programs were examined. The purpose of this research is to determine whether students are spending more or less time participating in an online course than in a traditional classroom. The discussion size (i.e., the number of words per discussion) was determined using the automatic word count function in MS Word. Once the word counts for each course section were determined, the average words per discussion were calculated. The authors used 180 words per minute to calculate the average reading time, based on the work of Ziefle (1998) and Carver (1985, 1990), in order to determine the average minutes per week a student spent reading the discussions. The study indicates that a typical, graduate-level, online, asynchronous discussion requires about one hour a week of reading time, and the time commitment for participatory activity is similar to that of traditional, face-to-face courses, given that it takes under two hours to compose initial messages and responses to the discussion prompt. Although these findings are informative, further research is recommended in the area of time spent on online course activities in terms of student hours earned to enable a direct focus on various student characteristics, such as English language competency and student level.